THE Relationship of Clean and Healthy Living Behaviors of Housewives with the Event of Diarrhea Children in Rega Village, Boawae District, Nagekeo Regency - Maria Yuliana Nago; Petrus Romeo; Helga J. N Ndun (Lontar : Journal of Community Health, 2023)
Diarrhea is one type of disease that originates from the environment and social behavior, especially about clean and healthy lifestyle. Data for the last three years shows the highest incidence of diarrhea in the working area of the Boawae Health Center. Diarrhea is influenced by several factors, namely mother's knowledge, use of clean water, handwashing with soap, and using healthy latrines. This study aims to identyfi the relationship between the clean and healthy living behaviuor of housewives and the development of diarrheal in children under the age of five in Rega Village Boawae District Nagekeo Regency. This research used a cross-sectional study design. The population of this study amounted to 271 people. The sample for this study consisted of 74 randomly drawn people. Data were analyzed using the chi-square test. Results showed that there was a relationship between maternal knowledge with the incidence of diarrhea (p=0.003), the use of clean water with the incidence of diarrhea (p=0.002), hand washing with soap with the incidence of diarrhea (p=0.008), and the use of healthy latrines with diarrhea incidence (p=0.005). The results showed that there was no association between attitudes and the incidence of diarrhea (p=0.358). Toddler mothers often practice cleanliness and a healthy lifestyle, especially using clean water, washing hands with soap, and using a healthy toilet to prevent diarrhea in babies, which you need to be able to do.